Simultaneous Electrochemical Detection of Pb and Cd by Carbon Paste Electrodes Modified by Activated Clay - Niraka Blaise; Hambate Gomdje Valéry; Raja Maallah; Mohamed Oubaouz; Bakary Tigana Djonse Justin; Edwin Andrew Ofudje; Abdelilah Chtaini (Journal of Analytical Methods in Chemistry)
Calcinated and acidified clay modified carbon graphite electrode was deployed in the simultaneous evaluation of traces of Pb2+ and Cd2+ in solution. After 5 minutes of accumulation in the circuit, the sensitivity of the electrode was evaluated in a solution of Na2SO4 (0.1 M) by square wave voltammetry on the one hand with Pb (II) and on the other hand with Cd (II). Several experimental conditions such as the composition of the carbon clay paste, the effect of preconcentration time, the sweeping speed, concentration effect, media pH, and interference ionic response to the electrochemical response of the working electrode were examined. It was observed that, after 5 minutes of preconcentration, detection limits of 0.15513 μmol·L−1 and 0.24227 μmol·L−1 were obtained for Pb2+ and Cd2+ in the electrolyte solution and 0.08438 μmol·L−1 and 0.46522 μmol·L−1, respectively, when tap water was used. The detection was effective by square wave voltammetry with a more intense current density with respect to lead.